Reflection of Marginality in The S.E.A. Write Awards Short Stories A.D. 2008-2017 - Kaewta, Kittisak; Kaencandra, Vajrindra (Trends of Humanities and Social Sciences Research, 2022)
The article entitled “Reflection of Marginality in the S.E.A. Write Awards Short Stories A.D. 2008-2017” aimed to analyze the reflection of marginality in the S.E.A. Write Awards short stories A.D. 2008-2017. The data was 4 titles 45 short stories by using Critical Discourse Analysis : CDA by Norman Fairclough. The results revealed that there were 7 reflections of marginality in the S.E.A. Write Awards short stories A.D. 2008 -2017. These were found 1) Social status and behavior 2) Economy and career 3) Health and public health 4) Geography 5) Social and culture 6) Education and 7) Political.